O texto literário nas aulas de língua inglesa na educação básica: concepções dos professores universitários - Cossa, Matheus (2016)
In the order to discuss and present ways to improve the English Teaching in Basic Education, this final paper aims to present a interpretative qualitative research which investigated four university teachers’ conceptions regarding the use of literary texts in English Language classes in Basic Education. To achieve this goal, data were collected through semi-structured interviews made with four teachers from a federal university located in the Southwest of Paraná. The answers of the interviews were recorded in audio and transcribed for further analysis. In the analysis, the collected data were organized into thematic topics, following the conceptions that were brought up by the educators. The results of the analysis showed that since literary texts are authtentic and endowed with rich cultural content, they can contribute to an English language teaching that values students’ integral education. In addition, literature enables the student to acquire culture and language skills simultaneously with the critical appropriation of the language.